Register Now

Lorem ipsum dolor sit amet, consectetur adipiscing elit. Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu. Fusce viverra neque at purus laoreet consequa. Vivamus vulputate posuere nisl quis consequat.

Solve the following simultaneous equations using Cramer’s rule. (3) x + 2y = –1 ; 2x – 3y = 12

Print or Save

Sol.     Given equation are
x   +   2y   =   –1
2x   –   3y   =   12

D   =  $\begin{vmatrix} 1 & 2 \\ 2 &- 3 \\ \end{vmatrix}$

=  (1 × –3) – (2 × 2)
=   –3 – 4
=   –7

∴       $D_x$  =  $\begin{vmatrix} -1 & 2 \\ 12 & -3 \\ \end{vmatrix}$

=  (–1 × –3) – (2 × 12)
=   3 – 24
=   –21

∴       $D_y$  =    $\begin{vmatrix} 1 & -1 \\ 2 & 12 \\ \end{vmatrix}$

=   (1 × 12) – (–1 × 2)
=    12 – (–2)
=    12 + 2

=    14

By Cramer’s Rule, we get;

∴         x   =   $D_x\over D$          and           y   =  $D_y\over D$

∴        x   =   $-21\over-7$                    ∴   y   =   $14\over -7$

∴        x   =    3                     ∴    y  =   –2

∴       (x, y) = (3, –2) is the solution of the  given equations.

SÉå cÉUÉÇMüÉåÇ uÉÉsÉå UåZÉÏrÉ xÉqÉÏMüUhÉ August 08 , 2018 0 Comments 185 views